Targeted inhibition of galectin-1 gene expression in tumor cells results in heightened T cell-mediated rejection: a potential mechanism of tumor-immune privilege - Rubinstein, Natalia (2004)
Despite the existence of tumor-specific immune cells, most tumors have devised strategies to avoid immune attack. We demonstrate here that galectin-1 (Gal-1), a negative regulator of T cell activation and survival, plays a pivotal role in promoting escape from T cell-dependent immunity, thus conferring immune privilege to tumor cells. Blockade of immunosuppressive Gal-1 in vivo promotes tumor rejection and stimulates the generation of a tumor-specific T cell-mediated response in syngeneic mice, which are then able to resist subsequent challenge with wild-type Gal-1-sufficient tumors. Our data indicate that Gal-1 signaling in activated T cells constitutes an important mechanism of tumor-immune escape and that blockade of this inhibitory signal can allow for and potentiate effective immune responses against tumor cells, with profound implications for cancer immunotherapy